Condom tamponade in the management of atonic postpartum hemorrhage - Santhanam, Ramya; Viswanathan, Radhamani Mavunkal; V., Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Postpartum hemorrhage (PPH) remains a leading direct cause of maternal death in both developed and developing countries. Millennium development goal of reducing maternal mortality rate cannot be achieved unless the prevention and treatment of PPH is prioritized. Objectives of the study were to study the efficacy of condom tamponade to arrest bleeding in cases of atonic PPH unresponsive to uterotonics. Methods: Prospective study conducted in the Kottayam Medical College where mothers who develop atonic PPH following childbirth unresponsive to uterotonics (after ruling out traumatic PPH) were included in study. Condom tamponade was applied in them and inflated with normal saline until the bleeding stops. Intrauterine drain was fitted with this to find out ongoing bleeding with tamponade in situ. The Condom tamponade was kept for 12-24 hrs and gradually deflated when bleeding ceased. Outcome measures were (1) Ability of condom catheter to stop bleeding; (2) Cases requiring further intervention; (3) Time required to stop bleeding and (4) Subsequent morbidity in terms of infection. Results: Of the 487 cases of atonic PPH, 61 required condom tamponade; bleeding controlled in 59 cases (96.7%); two patients (3.3%) needed further surgical intervention. No cases of maternal mortality due to PPH. No clinical evidence of intrauterine infection. Conclusions: The hydrostatic condom tamponade controls PPH quickly and effectively. It is simple, inexpensive, easily available, needs less expertise and life saving. Any healthcare provider may use this procedure as a timely measure to save the life of patients especially during referral to decrease ongoing loss.